Die Praxis und die Wirksamkeit der Wertevermittlung in der Katholischen Gemeinschaft Regnum Marianum - Semsey, Gábor; Török, Gábor; Csáky-Pallavicini, Zsófia; Horváth-Szabó, Katalin (European Journal of Mental Health, 2007)
Value Transmission Practice and Its Success within the Regnum Marianum Catholic Community: The authors studied the efficiency of the transfer of values within the Regnum Marianum community. At the beginning of the study they provide an overview of the principal knowledge pertaining to the transfer of values, mainly focusing on the criteria of successful value transmission, after which they present a short history of Regnum Marianum, its current operation and the chief features of its pedagogy. In connection to this they also touch upon how the criteria for successful value transfer are met at the Regnum. Following this they detail some results of a study examining the efficiency of value transmission at the Regnum. The study was based on the widely accepted Rokeach Value Survey. The study results are compared to the results of a nationwide survey, and they also examine the differences between the various age groups within the community. They conclude that value transfer can be considered relatively successful at the Regnum, especially considering the state of society, and the history of Hungary in recent decades.